National Crime Surveys Extract: Personal Crime Longitudinal Files, 1976-1982 - Innes, Christopher A. ([Verlag nicht ermittelbar], 1985)
The National Crime Survey (NCS) collects data on personal and household victimization through an ongoing national survey of households and household members. Only data for robbery and assaults are included in this dataset. There are two data files: Assault Victim Experiences, and Victim and Non-Victim Responses. Items included are time and place of occurrence, injuries suffered, medical expenses incurred, number, age, race, and sex of offender(s), relationship of offender(s) to victim, marital status, employment, military experience, and residency.